We Have Been Visited: Divine Encounter through the Lukan Benedictus (Luke 1:68–79) - Seal, David (The Biblical Annals, 2021)
Recent discussions of the Benedictus have focused on its function in Luke- Acts. However, little if no attention has been given to the persuasive force of the passage and how it may have functioned to create a divine encounter for the implied audience. This study will address this gap. Following a brief survey of Luke’s purpose and a discussion of the nature of prophecy, I will argue, first, that divine revelation was often cast in poetic form. Second, I will describe the poetic features of the Benedictus, emphasizing its divine nature. Third, I will explain the ancient perception that deities had a superior ability to name persons, places, and objects. I will follow this discussion with a listing of the divinely authored names in the Benedictus. Fourth, I will contend that the Old Testament vocabulary and the tone of confidence in Zechariah’s prophecy further enhances its divine nature. Finally, considering the above, I will explain how a skilled lector reading the prophecy to Luke’s original audience may have allowed them to experience something of the aural presence of God.